Keberhasilan Ekonomi Desa dan Sumber Daya Manusia terhadap Perekonomian Masyarakat - Azizatun Fitriani; M. Ibrahim Baihaqi; Muhammad Yasin (Journal of Islamic Economics and Finance, 2024)
This study aims to examine the relationship between village economic success and human resources on the community economy. The village economy is at the center of attention in the context of inclusive economic development, with quality human resources playing a key role in the process. Quantitative analysis methods were used in this research, with data collected through surveys and interviews in several selected villages. Research findings show a positive relationship between the level of village economic success, which is reflected in economic growth, access to basic services, and job creation, and the quality of human resources at the local level. These results provide important policy implications for sustainable and inclusive village economic development.